Diabetes Diagnosis and Control: Missed Opportunities to Improve Health: The 2018 Kelly West Award Lecture - Cowie, Catherine C. (Diabetes Care, 2019)
Diabetes is a prevalent condition in the U.S. and worldwide, with expanding impact over time as it affects progressively younger ages as well as older ages as people live longer. Costs of diabetes to those affected and to society as a whole continue to increase. Costs are realized through daily treatment regimens throughout life to control glycemia and other risk factors for complications as diabetes progresses, diabetes complications and disability and their treatments, health care visits and hospitalization, and as indirect costs via lower quality of life and lost productivity. Diagnosing diabetes is key to affording the opportunity to treat diabetes, and diabetes control is key to reducing the risk of complications. Yet the magnitude of undiagnosed diabetes and poor control of diabetes is large. And just as certain subgroups of the population are affected disproportionately by diabetes and diabetes complications, so are they affected disproportionately by undiagnosed diabetes and poor control. This review addresses the epidemiology of undiagnosed diabetes and diabetes control, largely covering their magnitude, demographic variation, trends over time, and predictors. For diabetes control, it focuses on control of A1C, blood pressure, and lipid levels, although there are many other facets of diabetes control and preventive care that also could be examined. The review is based predominantly on data from the National Health and Nutrition Examination Survey (NHANES), a U.S. health survey that includes both an interview and examination component that has been conducted continuously since 1999 and episodically for decades earlier. The interview elicits self-reported health responses pertaining to diabetes and other medical conditions and an examination that measures glycemic indicators, blood pressure, and lipids, which provide much of the material presented herein. Data from other studies are also presented and described.